Morphological characterization of an ethnographic sample of maize (Zea mays L.) ball race of Oaxaca - Ramírez Jaspeado Araceli; García de los Santos Gabino; Carballo Carballo, Aquiles; Castillo González Fernando; Serratos José Antonio; Cadena Iñiguez Jorge (Revista Mexicana de Ciencias Agrícolas, 2018)
Based on the needs, interests, practices and knowledge of human populations, there has been shaped and maintained the genetic diversity of maize (Zea mays L.). Special uses of this resource have determined selection criteria for domestication, and have gained importance in the field of conservation of plant genetic resources, to be also a way of generating income to families. A special use of maize is constituted by the "tlayuda" tortilla over 30 cm in diameter and "long" shelf life; famous in Central Valleys of Oaxaca, Mexico, using mostly grain from ball race. The objective of this work was the morphological characterization of 108 accessions of maize obtained in 17 locations from Zimatlán Districts, Ejutla and Ocotlán in Central Valleys of Oaxaca in 2011. Nine traits from the cob and grain were considered, five relations between these traits. It was applied a principal component analysis, cluster and using UPGMA grouping and as similarity measure was employed the Euclidean distance average. It was observed the formation of three major groups with preponderance of ball race accessions, but also, presence of Pepitilla and in less extent Tuxpeño. The variability found, refers to the presence of racial complexes. It is possible to suggest that the result of this study allows the discrimination or racial inclusion in the preparation of tortillas tlayuda and propose criteria for a possible designation of origin of such product and thus favor the preservation of native maize.